Perceptions and experiences with eating disorder treatment in the first year of COVID‐19: A longitudinal qualitative analysis. Issue 1 (27th December 2022) - Goode, Rachel W.; Godoy, Sarah M.; Wolfe, Hannah; Olson, Katie; Agbozo, Bridgette; Mueller, Abigail; Noem, Taylor; Malian, Hannah; Peat, Christine M.; Watson, Hunna; Thornton, Laura M.; Gwira, Rebecca; et al.
Abstract: Objective: The COVID‐19 pandemic created significant challenges in accessing and receiving treatment for individuals with eating disorders (EDs). The purpose of this study is to explore perceptions of and experiences with ED treatment during the first year of the pandemic among individuals with past and self‐reported EDs in the United States. Methods: Online surveys were administered to adults ( N = 510) with a past or current self‐reported ED at 13 timepoints between April 2020 and May 2021. Using longitudinal qualitative analysis, 5651 free‐text responses were examined to capture experiences with ED treatment and generate inferences of change over time. Results: We categorized results into four sequential, temporal quarters and identified patterns that explained participants' perceptions of facilitators, barriers, and experiences with ED treatment over time: Quarter 1. Treatment Disruption and Reorienting Recovery; Quarter 2. Accumulating COVID‐19 Stress and Virtual Treatment Woes; Quarter 3. A Continuation of Inadequate Care; and Quarter 4. Ongoing Adaptation and Adjustment to Uncertainty. Participant experiences were marked by numerous barriers to accessing care, challenges adjusting to virtual treatment, unmet treatment needs, and beginning acceptance of telehealth. Discussion: Our findings present a timeline to help evaluate challenges related to navigating the switch to virtual care which created significant disruption to ED recovery. Participants spent much of the first year trying to adjust to unemployment, loss of insurance, and lack of access to in‐person treatment. Future research should identify additional strategies to improve the receipt and experience of care for EDs. Public Significance: Our findings suggest that individuals with eating disorders were significantly challenged by accumulating COVID‐19 stress, worsening symptomatology, and limited access to effective treatment during the first year of the pandemic. This knowledge can guide clinicians, treatment centers, and policy makers in addressing the behavioral health needs of individuals impacted by disordered eating amidst emergent public health crises.